2010
DOI: 10.1155/2011/956864
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Paracetamol Mediated by MgB2 Microparticles Modified Glassy Carbon Electrode

Abstract: A MgB 2 microparticles modified glassy carbon electrode (MgB 2 /GCE) was fabricated by adhering microparticles of MgB 2 onto the electrode surface of GCE. It was used as a working electrode for the detection of paracetamol in 0.1 M KH 2 PO 4 aqueous solution during cyclic voltammetry. Use of the MgB 2 /GCE the oxidation process of paracetamol with a current enhancement significantly by about 2.1 times. The detection limit of this modified electrode was found to be 30 µM. The sensitivity under conditions of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 5 publications
8
49
0
Order By: Relevance
“…Bi2O3 micro-particles deposited onto glassy carbon electrode have been successfully used as the electro-catalyst in the electrochemical oxidation of ascorbic acid [19]. It has also been applied as a photocatalyst for the removal of other compounds, such as some organic dyes and pigments, 4-chlorophenol and gaseous NO and HCHO [20][21][22][23][24][25].…”
Section: Ho2• + H2o2→ •Oh + H2o + O2 Eq (3)mentioning
confidence: 99%
“…Bi2O3 micro-particles deposited onto glassy carbon electrode have been successfully used as the electro-catalyst in the electrochemical oxidation of ascorbic acid [19]. It has also been applied as a photocatalyst for the removal of other compounds, such as some organic dyes and pigments, 4-chlorophenol and gaseous NO and HCHO [20][21][22][23][24][25].…”
Section: Ho2• + H2o2→ •Oh + H2o + O2 Eq (3)mentioning
confidence: 99%
“…12 indicates that TiInCrO 6 modified glassy carbon electrode has larger adsorption-desorption and high electrochemical reaction than that of TiO 2 nanomaterial. A few literature information has indicated that glassy carbon electrodes modified with metal ion and carbon materials are created to achieve enhanced in comparison to bare GCE (Subash et al 2013a, b;Zidan et al 2010;Radhi et al 2010;Chandraboss et al 2015). The result thus suggests that the occurrence of could increases current and improves the relation electron transferred by TiInCrO 6 nanomaterial.…”
Section: Cyclic Voltammogram (Cv)mentioning
confidence: 97%
“…In addition, previous literature has also demonstrated that bismuth oxide-modified electrode has a special sensitivity in detecting paracetamol (Zidan et al 2011), which is a small molecule with a skeleton of phenol. While in this work, as it has been said previously, the main difference of green and black teas is their different concentrations in phenolic compounds.…”
Section: The Analysis Of Bi 2 O 3 -Modified Nickel Foam Electrodementioning
confidence: 98%
“…Bismuth oxide, which is known as an important transition metal oxide, has been used for a range of applications (Hwang et al 2008;Li and Yan 2009;Zidan et al 2011Zidan et al , 2010 because of its special energy band gap and photoconductivity. In this system, the electrode reaction of Bi 2 O 3 is:…”
Section: The Analysis Of Bi 2 O 3 -Modified Nickel Foam Electrodementioning
confidence: 99%